1989
DOI: 10.1121/1.398098
|View full text |Cite
|
Sign up to set email alerts
|

The crevice model of bubble nucleation

Abstract: The crevice model for heterogeneous nucleation of bubbles in water in response to a decreasing liquid pressure is studied. The model neglects gas-diffusion effects and is therefore more suited for acoustic than for flow cavitation. It is argued that previous work has overlooked the essential requirement of unstable growth of the interface in the crevice. As a consequence, the available results are incorrect in some cases. Another feature of the model which is considered is the process by which the interface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
192
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 0 publications
4
192
0
6
Order By: Relevance
“…Likewise, Strasberg [6] found that static pre-pressurization up to a few bar increased the tensile strength by about 4 bar per bar of pressurization, while, at a subsequent pressure decrease, the tensile strength went down by only as much as the pressure reduction, the testing being made ultrasonically. The crevice model has received much attention and has been developed notably in [7,8]. However, though most surfaces have an irregular shape on a micrometre level [9], hydrophobic surfaces with crevices are not characteristic of solid surfaces generally.…”
Section: Classical Models Of Cavitation Nucleimentioning
confidence: 99%
“…Likewise, Strasberg [6] found that static pre-pressurization up to a few bar increased the tensile strength by about 4 bar per bar of pressurization, while, at a subsequent pressure decrease, the tensile strength went down by only as much as the pressure reduction, the testing being made ultrasonically. The crevice model has received much attention and has been developed notably in [7,8]. However, though most surfaces have an irregular shape on a micrometre level [9], hydrophobic surfaces with crevices are not characteristic of solid surfaces generally.…”
Section: Classical Models Of Cavitation Nucleimentioning
confidence: 99%
“…Extensive research has been carried out on the topic over the years by numerous groups (see e.g. Harvey et al 1944;Fox & Herzfeld 1954;Apfel 1970;Kodama et al 1981;Atchley & Prosperetti 1989;Rood 1991;Meyer, Billet & Holl 1992;Milton & Arakeri 1992;Vinogradova et al 1995;Gindroz & Billet 1998;Liu & Brennen 1998;Arndt & Maines 2000;Mørch 2000;Hsiao, Chahine & Liu 2003). In the vast majority of engineering applications in which cavitation takes place, it can be argued that heterogeneous nucleation dominates, since all working fluids are expected to have a certain level of contamination and impurities.…”
Section: Bubble Nucleationmentioning
confidence: 99%
“…Second, they are potential candidates to explain various phenomena associated with the liquid-solid interface, such as liquid slippage at walls [13,14,15] or the anomalous attraction of hydrophobic surfaces [1] in water. In addition, heterogeneous cavitation usually starts from gaseous nuclei at solid surfaces (see [16] and references therein), and surface nanobubbles are suggested as potential inception sites [7,17,18]. However, apart from convincing experimental evidence for the existence and stability of nanobubbles, still little is known.…”
mentioning
confidence: 99%